Processing, Financial, And Swot Analysis - Alamsyah, Rizal; Budhiono, Arief; Yang Setiawan, Yang; Rinaldi, Herry (Balai Besar Industri Agro, 2002)
This study described about analysis of processing ,financial and SWOT (strength weakness,opportunities,and threats) for jackfruitÂ vacuum frying processing for vacuum frying of jackfruit the frying condition (pressure and temperature ) frying rate,and organoleptik test were investigated.the jackfruit are submerged in heated solid frying oil induce vavorization of the water from the jackfruit . this was conducted under vacuum pressure of-70 cm Hg ,and temperature level of 75 0C and 80 0CÂ such condition was done to minimize the heat used and therefore reduce changes in composition, color ,taste, and flavor of the jackfruit the results showed that the product has low moisture content of 3.58% ( wet basis)with the taste,flavor ,color, and volume similar to the fresh jackfruit .this experiment was conducted using 3 kg of jackfruit ,the yield of the product was 22% and the total water removal was 2510 ml. it finalcial analysis was conducted to evaluate the financial viability of jackfruit processing.financial analsyis of the jackfruit production capacity of 30 kg per day showed that NPVÂ (net present value) was rp 52.391.000 which was bigger than investment cost,IRR( internal rate return) was 51% and PBP(pay back period